1985
DOI: 10.1111/j.1365-3040.1985.tb01383.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell-cell communication in the leaves of Commelina cyanea and other plants

Abstract: The fiuorescent probes 6-carboxylluorcscein and lucifer yellow CH which do not pass the plastnalemma have been used to examine cell-to-ccU cotnmunication in the \sai oi Commelina cyanea. Dye movement from ccll-to-cell occurs in epidermal, spongy and palisade mesophyll, and vascular cells. Dye movement between these tissues was also found. Hence, the epidermis, spongy and palisade mesophyll cells, and vascular tissue are all linked in a continuous symplast. However, dye injected into the epidermal cells rarely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
1

Year Published

1990
1990
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 21 publications
2
28
1
Order By: Relevance
“…Targeting of 3a MP:GFP to truncated plasmodesmata between the epidermal and mature guard cells was unexpected, because these plasmodesmata apparently do not have intercellular transport functions (Erwee et al, 1985;Palevitz and Hepler, 1985;Ding et al, 1997). Nevertheless, this finding implies that protein targeting to plasmodesmata is an autonomous function of a cell and is not necessarily coupled to protein translocation through plasmodesmata or protein release from plasmodesmata for import into a neighboring cell.…”
Section: Discussionmentioning
confidence: 86%
“…Targeting of 3a MP:GFP to truncated plasmodesmata between the epidermal and mature guard cells was unexpected, because these plasmodesmata apparently do not have intercellular transport functions (Erwee et al, 1985;Palevitz and Hepler, 1985;Ding et al, 1997). Nevertheless, this finding implies that protein targeting to plasmodesmata is an autonomous function of a cell and is not necessarily coupled to protein translocation through plasmodesmata or protein release from plasmodesmata for import into a neighboring cell.…”
Section: Discussionmentioning
confidence: 86%
“…Erwee et al (9) and Madore et al (22) examined tissue in which the lower epidermis was removed but the spongy mesophyll remained and obscured the veins; dye was seen to travel in the direction of the veins, but the cell type(s) carrying the dye could not be identified. Van Does dye-coupling indicate that phloem loading is symplastic?…”
Section: Dye-coupling Studiesmentioning
confidence: 99%
“…It was concluded that the mesophyll apoplast in pea has a relatively low capacitance as an ion reservoir. Apoplastic K+ content was found to be highly sensitive to changes in xylem solution concentration.The apoplast within leaf tissue constitutes a potentially important pathway for K+ transport between vascular and mesophyll tissues (6,22,23) accumulate extracellulary within the vascular bundles, whereas lower concentrations would exist within the cell wall of mesophyll tissue more distant from the minor veins.The specific role(s) ofthe apoplast as related to K+ transport and accumulation within leaf lamina tissue cannot be fully elucidated without quantitative analysis of extracellular K+ content and concentration (20). Several indirect approaches have been reported for collection of apoplastic sap and estimation of ionic concentrations including analysis of xylem exudates, vacuum perfusion of leaf lamina discs (1), and pressure dehydration of leaves (14).…”
mentioning
confidence: 99%
“…The apoplast within leaf tissue constitutes a potentially important pathway for K+ transport between vascular and mesophyll tissues (6,22,23) accumulate extracellulary within the vascular bundles, whereas lower concentrations would exist within the cell wall of mesophyll tissue more distant from the minor veins.…”
mentioning
confidence: 99%
See 1 more Smart Citation